Implementation of FLEGT Licensing Scheme in Deforestation Law Enforcement: Improvements and Handling in Indonesia - Muhammad Mutawalli; Maskun Maskun; Harlida Abdul Wahab; Andi Tenri Yeyeng (Unissula, 2023)
This study aims to determine the implementation of the Forest Law Enforcement, Governance, and Trade (FLEGT) licensing scheme in Indonesia, focusing on its improvements and handling in relation to deforestation law enforcement. The research method used is qualitative, with an empirical juridical, statutory, and contextual approach. The results of this study indicate that aspects of environmental law enforcement in Indonesia have not yet come to light. The responsible authorities and powers exhibit a tendency to supersede established regulations of environmental law enforcement regarding procedural requirements, remedies, and sanctions. Consequently, reforestation schemes and forestry restoration permits, which are intended to counteract the effects of deforestation, have proven to be ineffective. This ineffectiveness can be attributed to the ongoing industrial forestry activities carried out by companies and entrepreneurs, which lack the requisite procedures for ensuring accountability in environmental restoration.